Efektivitas Program Experiential Based Counseling Untuk Mengembangkan Kompetensi Intrapersonal dan Interpersonal - Asep Rohiman Lesmana (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
The research is motivated by the lack of intrapersonal and interpersonal competence of Universitas Pendidikan Indonesia’s students. The research aimed to test the effectiveness of experiential-based counseling program to develop intrapersonal and interpersonal competencies of students. The research using qualitative and quantitative approach with quasi-experimental methods, and with the equivalent time series design. The Study was conducted in the Universitas Pendidikan Indonesia with 92 s participants Student French Language participants using non-random sampling technique. The instrument used a likert scale of intrapersonal and interpersonal. Data were analyzed using paired t-test. The results showed that experiential-based counseling program effective to develop intrapersonal and interpersonal competencies students. Overall there was an increase intrapersonal competence of students with an average score of 12.39%, and improved interpersonal competence of students with an average score of 17.93%. This research can be used as a reference for the guidance and counseling services unit, lecturer and counselors at universities to develop the intrapersonal and interpersonal competence of student.